Rocket Investigation of Current Closure in the Ionosphere (RICCI): A novel application of CubeSats from a sounding rocket platform. Issue 1 (1st July 2020) - Cohen, Ian J.; Anderson, Brian J.; Bonnell, John W.; Lysak, Robert L.; Lessard, Marc R.; Michell, Robert G.; Varney, Roger H.
Abstract: The Rocket Investigation of Current Closure in the Ionosphere (RICCI) sounding rocket mission concept will use the novel deployment of multiple CubeSats as miniature sub-payloads to obtain the first direct in-situ measurement of ionospheric closure currents. These ionospheric currents are critical to understanding the nature of atmosphere-ionosphere-magnetosphere coupling and have relevance to space weather parameters such as ionospheric densities, thermospheric heating, and satellite drag. Previous attempts to measure these ionospheric closure current in-situ have been limited by poor attitude knowledge resulting in large uncertainties in the magnetic field measurement that compromise the ability to measure the gradient of the magnetic field beyond the precision necessary to resolve the current densities. To address this, RICCI uses dedicated star trackers and currently-available CubeSat subsystems to obtain the high-precision attitude knowledge necessary to directly measure these elusive currents.